Establishment Of Local Diagnostic Reference Levels (Drls) For Ct Examination And Assessment On Current Clinical Ct Practice At Amdi, Usm - Razali, Mohd Amir Syahmi Mat (2021)
The main focus of this research is to propose and establish the local diagnostic reference levels (LDRLs) for the most frequent CT examinations performed at Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia (USM), Penang, Malaysia. A total of 1444 CT examinations from January 2015 until December 2018 were included in a retrospective CT dose survey. Based on CT examination protocols, the proposed LDRLs were established at 50th (achievable dose, AD) and 75th (DRLs) percentile of CT dose index distribution which are CTDIvol, CTDIw, and dose length product, DLP. Comparison between established LDRLs with the national DRLs (NDRLs) from Ministry of Health (MOH) Malaysia and other recent international DRLs were performed, respectively. The most frequent CT examinations performed at AMDI were thorax-abdomen-pelvis (TAP) CT (46.95 %), trailed by pelvis CT (15.44 %), abdomen-pelvis (AP) CT (10.46 %), and brain CT (8.31 %). Most of the LDRLs surpassed the NDRLs and other recent international DRLs. From the radiation dose audit, most of the 2018 CT dose data exceeded the LDRLs; TAP, pelvis, AP, brain, and abdomen CT examinations were noted to have higher CT dose data. There were no significant differences (P-values = > 0.05) between most of 2018 CT data that exceed and below the proposed LDRLs. The main factors that contribute to higher dose were due to higher number of CT sequences, higher tube current (mAs) settings, and error in patient positioning. The LDRLs must be established to reduce unjustified radiation exposure incidence and to optimise the CT dose to the patients. For improvement of current local practice, the local dose distribution must always be revised regularly.